An evaluation of Retaine™ ophthalmic emulsion in the management of tear film stability and ocular surface staining in patients diagnosed with dry eye - Ousler, George (Clin Ophthalmol, 2015)
A single-center, open-label study consisting of two visits over the course of approximately 2 weeks was conducted to evaluate the efficacy of Retaine™ ophthalmic emulsion in improving the signs and symptoms of dry eye. Forty-two subjects were enrolled and received 1–2 drops twice daily of Retaine™ beginning at the first visit (day 1) and ending at the second visit. Subjects were instructed to complete a symptomatology diary twice daily prior to drop instillation through the morning of the second visit. Ocular sign and symptom assessments, visual acuity procedures, and comfort assessments were conducted during both visits. A statistically significant reduction was observed in mean breakup area on the second visit between the predose time and the postdose time (P=0.026). On the second visit, subjects had significantly less corneal fluorescein staining in the superior (P=0.002), central (P=0.017), corneal sum (P=0.011), and all ocular regions combined (P=0.038) than on the first visit. On the second visit, statistically significant reductions in dryness (P<0.001), grittiness (P=0.0217), ocular discomfort (P=0.0017), and all symptoms (P<0.001) were also seen as measured by the Ora Calibra™ Ocular Discomfort and 4-Symptom Questionnaire (0–5 scale). Subjects reported a statistically significant improvement in their abilities to work with a computer at night (P=0.044). Mean drop comfort scores ranged from 1.29–1.81 on the Ora Calibra™ 0–10 Drop Comfort Scale, on which 0 is very comfortable and 10 is very uncomfortable. Retaine™ demonstrates promising results as a novel artificial tear option for individuals suffering from dry eye. The unique mechanism of action of Retaine™ provides enhanced comfort and improves the quality of life of dry eye subjects while reducing the ocular signs of dry eye.